EFL Learners' Reading Comprehension Challenges and Strategies: A Case Study of Champasack University in Laos - Khanngeun Vongsawath; Yeny Prasitiwi; Nur Hidayat (Journal of English Language Teaching and Linguistics, 2025)
Reading comprehension is a primary skill in English as a Foreign Language (EFL) learners, but many of them face challenges that impede their language learning. This study investigates reading comprehension problems experienced by EFL learners at Champasack University (Laos), and suggests solutions to remediate these problems. A qualitative case study was employed, involving semi-structured interviews with 10 final-year students to explore their experiences and coping strategies. This study highlights the important barriers learners face such as limited vocabulary, complex grammatical structures, and summarizing and identifying main ideas. Strategies such as using a dictionary, context-guessing, and collaborating with peers are employed, but these are often not enough in the absence of structured support. Although they elevate pressing interest in redressing the factors that put children at risk for literacy challenges, with a focus on systematic vocabulary instruction focused on explicit instruction and teaching cognitive and metacognitive strategies for teaching reading comprehension, the results also suggest the following possible interventions: Also, using digital tools and collaborative learning activities can alleviate reading anxiety and enhance learner motivation, creating a more bolstered learning environment. The study reaffirmed the need for targeted pedagogical intervention and that future work might discover how to make such strategies more effective over the long term and the part digital literacy plays in EFL pedagogy. Our findings provide valuable insights for educators and policy-makers, who might find it helpful in possibly improving reading comprehension outcomes for EFL learners across different learning contexts.